The Influence of Audit Committee, Firm Size, and Sales Growth Toward Tax Avoidance in Coal Mining Companies Listed on the Indonesia Stock Exchange - Sitompul, Thomson; Aldora, Velda (Universitas Pelita Harapan, 2024)
Coal is valued for its energy content and since the 1880s has been widely used to generate electricity. In Indonesia coal mining sector is one of the drivers of economic development, because of its role as a provider of energy resources indispensable for the economic growth of a country. The research designs used in this research are quantitative. There are 23 companies which are taken as the number of samples with period from 2019-2022. The data analysis method includes: descriptive statistic, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, validity test and hypothesis test. Based on the data analysis, this research reveals that Audit Committees have a positive and significant influence towards Tax Avoidance in Coal Mining Companies Listed on The Indonesia Stock Exchange, Firm Size have a positive and significant influence towards Tax Avoidance in Coal Mining Companies Listed on The Indonesia Stock Exchange and Sales Growth do not have influence towards Tax Avoidance in Coal Mining Companies Listed on The Indonesia Stock Exchange.